Nutritional, phenolic and in vitro digestion characteristics of dried grape pomace processed with different micronization/air-classification protocols - Aristide Maggiolino; Roberta Greco; Federica Blando; Eleni Tsiplakou; Elisabetta Casalino; Pasquale De Palo (Italian Journal of Animal Science)
Grape pomace requires drying to prevent spoilage and ensure year-round use. This study evaluates the nutrient composition, in vitro digestibility, gas production, and phenolic content of dried grape pomace processed with different micronization and air-classification techniques. Dried grape pomace was micronized at frequencies of 85 Hz (LH) and 170 Hz (HH), then air-classified at pressures of 200 psi (LP) and 240 psi (HP) into coarse (G), middle fine (F1), and fine (F2) fractions. The four experimental groups were: low Hz low PSI (LH-LP), low Hz high PSI (LH-HP), high Hz low PSI (HH-LP), and high Hz high PSI (HH-HP). The HH-HP treatment resulted in the highest crude protein (p < 0.01) in the F1 fraction, and the LH-LP treatment showed the highest ether extract content (p < 0.01) in the F2 fraction. Additionally, the HH-HP method produced the highest crude fibre (p < 0.01) in the G fraction. Rutin was more concentrated in the G fraction and lesser in F2 (p < 0.05). The highest phenolic concentration was recorded in the F1 fraction under high micronization (p < 0.05), while G fraction had the lowest Folin values (p < 0.05). These findings suggest that fine fractions enriched in polyphenols and antioxidant activity, offer promising benefits for animal feed applications by potentially improving feed functionality and health-promoting properties. In conclusion, micronization and air-classification improved the protein content of finer grape pomace fractions but slightly reduced protein digestibility, likely due to interactions with phenolics or increased fibre. Overall, the optimised processing techniques show potential to make grape pomace a sustainable and functional feed ingredient for ruminants.